DETERMINANT MODELS AFFECTING FINANCIAL PERFORMANCE AND STOCK RETURN COMPANIES REGISTERED IN INDONESIA STOCK EXCHANGE - Sudarno, Sudarno; Suyono, Suyono; Yusrizal, Yusrizal; Tambunan, Johannes (Jurnal Aplikasi Manajemen, 2021)
This research aims to analyze the effect of Capital Adequacy Ratio (CAR), Operating Expenses to Operating Income Ratio (BOPO), Loan to Deposits Ratio (LDR), Net Interest Margin (NIM), and Non-Performing Loan Ratio (NPL) variables on ROA and Stock Return of Banks That Listed in the Indonesia Stock Exchange. The population in this research is all banks listed on the Indonesia Stock Exchange. At the same time, the samples are 30 companies. The sampling uses the purposive sampling method. Secondary data was obtained in the Indonesia Stock Exchange and Yahoo! Finance. The independent variables used are CAR, BOPO, LDR, NIM, and NPL. The data analysis technique used is multiple linear regression analysis by SmartPLS software. This research indicates that the LDR, NIM, and NPL variables have a significant effect on ROA. The CAR, BOPO, and NPL variables have a significant effect on Stock Return. The predictive ability of the independent variables (CAR, BOPO, LDR, NIM, and NPL) on ROA is 59.5%, as indicated by the value of Adjusted R Square is 59.5%, while the remaining is 40.5% influenced by other variables not included in this research. The independent variables (CAR, BOPO, NIM, and NPL) on Stock Returns have 13.3% of Adjusted R Square while the remaining is 86.7% influenced by other variables.